Identification of Aquatic Biota Using the Biotilik Method to Assess Water Quality of the Genteng River as Biology Learning Material at Muhammadiyah 10 Senior High School Surabaya - Salim Bahrisy; Yuni Gayatri; Laga Yudhistira (Florea : Jurnal Biologi dan Pembelajarannya, 2025)
The increasing pollution of rivers due to domestic activities and urbanization highlights the importance of biology-based water quality monitoring. This study aims to assess the water quality of the Genteng River (Kalimas) in Surabaya using the biotilik method with macroinvertebrates as bioindicators. The research was conducted descriptively with a mixed quantitative and qualitative approach. Data were collected through observation, sampling, and identification of macroinvertebrates based on the Biotilik guidelines. The identification results showed that the species composition was dominated by organisms tolerant to pollution. The average biotilik score of 1.5 classified the water quality in the Heavily Polluted category. These findings reflect a severely degraded river ecosystem. This study holds great potential to be utilized as contextual learning material in project-based Biology education, aiming to enhance students environmental awareness and critical thinking skills.